2022
DOI: 10.1007/s10340-022-01495-3
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs shape social immunity: a potential target for biological control of the termite Reticulitermes chinensis

Abstract: Eusocial insects can employ various behavioural and physiological disease defences to avoid, resist and tolerate pathogen infections in their closely related and packed colonies, termed social immunity. Recent studies have shown that several molecules serve insect social immunity, including chemical odours, insect venoms, immune-related proteins, etc. However, whether and how microRNAs (miRNAs), whose precursors are processed by Dicer-1, drive social immunity in insect colonies is still unknown. Here, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…54 After treatment with miR-71-5 simulation, the mortality rate of infected termite populations significantly increased during fungal contamination. 55 In our study, we showed that knockdown of the miR-184-3p target gene Ken promotes RBSDV transmission by L. striatellus, suggesting that miR-184-3p antagomir treatment could enhance the expression of Ken to inhibit virus transmission.…”
Section: Discussionmentioning
confidence: 63%
“…54 After treatment with miR-71-5 simulation, the mortality rate of infected termite populations significantly increased during fungal contamination. 55 In our study, we showed that knockdown of the miR-184-3p target gene Ken promotes RBSDV transmission by L. striatellus, suggesting that miR-184-3p antagomir treatment could enhance the expression of Ken to inhibit virus transmission.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, throughout the bodies of the termites, we found that miR-7885-5p, miR-252b, and miR-71a-5p were significantly upregulated during fungus–termite interaction. An miR-71a-5p mimic has been reported to make termites more vulnerable to entomopathogenic fungi . Here, miR-7885-5p and miR-252b mimics increased the susceptibility of termites to entomopathogenic fungi.…”
Section: Discussionmentioning
confidence: 83%
“…Among the 13 miRNAs, miR-7885-5p ( n = 5, p < 0.05, Wilcoxon test) and miR-252b ( n = 6, p < 0.05, Wilcoxon test) were verified to be significantly upregulated in fungus-infected termites (Figure A,B). According to the sequences of the miRNAs, miRNA mimics, small double-stranded RNAs, were synthesized using the T7 RNAi transcription system . Both of the miR-7885-5p and miR-252b mimics had no impact on the mortality of naive termites (mortality = 0) but significantly increased the mortality of fungus-infected termites (miR-7885-5p mimic + fungus vs GFP siRNA + fungus: χ 2 = 11.558, p < 0.01; miR-252b mimic + fungus vs GFP siRNA + fungus: χ 2 = 10.450, p < 0.01; Kaplan–Meier method) (Figure C,D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations